Frequency of Direct Funduscopy Upon Initial Encounters for Patients with Headaches, Altered Mental Status, and Visual Changes: A Pilot Study - Golombievski, Esteban; Doerrler, Michael W.; Ruland, Sean D.; McCoyd, Matthew A.; Biller, José (Frontiers in Neurology, 2015)
Background: Residents’ funduscopy skill is an important topic for medical education. Objective: To provide a snapshot of the performance of direct funduscopy (DF) as part of the initial clinical assessment among different faculty physicians and residents from Internal Medicine (IM), Emergency Medicine (EM) and Neurology (N). Methods: Retrospective study of 200 randomly reviewed charts of patients (> 18 years) presenting either to the ED, inpatient units or outpatient clinics from January 2001 to July 2013, with corresponding ICD-9 codes for headaches, altered mental status and visual changes. Results: Whereas the Neurology Service was the one who performed most DF upon initial evaluation, DF is infrequently done throughout services independent of inpatient or outpatient location. More than half of patients (66%) presenting with visual symptoms had evaluation done by Ophthalmology. Conclusions: A more robust teaching of DF should be included among the basic clinical competencies during Medical School and Neurology Residency training.